Sprecific of distribution of chemical elements in graphite inclusions in as‑cast and deformed ductile cast iron - A. I. Pokrovsky; S. V. Grigor’ev (Литьë и металлургия, 2024)
The knowledge about distribution of chemical elements in graphite is crucial for understanding the mechanism of nucleation and growth of graphite inclusions during high‑temperature crystallization of a cast iron melt. It is also important for understanding the mechanisms of subsequent plastic deformation of cast iron.The specificity of the electron probe microanalysis (EPMA) of spherical graphite inclusions in cast iron, which is connected with a selection of the specimen’s cross‑section to be studied, is described. The most reliable and informative results are obtained when the graphite inclusion is cut by a plane of the metallographic section exactly in the middle.Comparative EPMA is performed of the profiles of chemical elements over a cross‑section of graphite inclusions in the ascast and deformed (by hot extrusion) ductile iron. It is found that in the as‑cast state, the center of inclusions, in addition to the main element (carbon), features anomalies in the concentration profiles of a number of elements. Magnesium, silicon, sulfur, oxygen and sometimes iron exhibit increased content in the center. This can be attributed to the presence of oxide, sulfides and oxysulfide microparticles in the cast iron melt during crystallization (or inclusions of silicon‑containing ferrite) on which graphite inclusions subsequently grow.In the deformed cast iron, anomalies in the concentration distribution of elements in the inclusions are largely eliminated and their distribution becomes more uniform. The higher the reduction ratio, the larger is the homogeneity of the chemical composition. To some extent, the heterogeneity of the composition distribution is still found in the longitudinal section at deformation with the reduction ratio of 60 %. For the reduction ratio of 80 %, in cross section the inclusion becomes almost completely homogeneous in chemical composition over the in cross section.